India story - Pani, Niranjan (New Delhi, 2010)
Change is only constant. Everything changes. India observed its 60th year of adoption of Constitution in 2009. A number of changes occurred due to Constitutional Amendments with multiple effects. Necessarily, the missions of Amendments are change and development directed. Moreover, the Amendments reflect the wisdom of Leadership of Prime Ministers through ages. Contexually, the book INDIA STORY Amendmenta and Search for An Alternate Model portrays a picture of current India, Amendments to Constitution of India in detail and changes through Amendments. Above all an analaysis is presented in the coveted book as to the need of Presidential Type of Government- an Alternate Model - for India in the wake of strained performance of present Parliamentary system. Also the new model is suggested owing to its merits of stability, Structure, cost effectiveness and other parameters of performance. And the future changed model may lead India into Bhatat Nirman with 'Agenda Development'. Further the work will provide scope for planners, political Leaders to debate the issue and provide a suitable model for India.
Keywords: Constitutional amendments